Jones in the cognitive niche. The metaphilosophical problem of writing in the linguistic approaches to mind - Manca, Danilo (Mechane, 2024)
In this essay, I adopt a metaphilosophical approach to investigate the role of writing in the context of the development of a linguistic approach to the philosophy of mind. In the first section, I portray the 20th-century analytic and pragmatist philosophy as unitedly committed to countering the representationalist image of the origin of conceptual activity. The aim is to show how this tradition is, however, internally divided between those who do not ascribe an instrumental role to language and those who, conversely, continue to describe language in terms of a tool. In the second section, I suggest that the difference between the two positions lies in the choice of adopting oral or written language as models for interpreting the relationship between mind and language. In the third, I ask whether writing can be interpreted as a niche-building activity.